Higher-Order Riesz Transforms in the Inverse Gaussian Setting and UMD Banach Spaces - Jorge J. Betancor (Hindawi Limited, 2021)
In this paper, we study higher-order Riesz transforms associated with the inverse Gaussian measure given by πn/2ex2dx on ℝn. We establish Lpℝn,ex2dx-boundedness properties and obtain representations as principal values singular integrals for the higher-order Riesz transforms. New characterizations of the Banach spaces having the UMD property by means of the Riesz transforms and imaginary powers of the operator involved in the inverse Gaussian setting are given.